Amrikan : 125 recipes from the Indian American diaspora - Shah, Khushbu (W. W. Norton & Company, Inc., 2024)
"What is Indian food in America?" In her eagerly anticipated debut cookbook, acclaimed food writer Khushbu Shah injects an electric and irresistible energy into the story of Indian food, with 125 recipes inspired by the cooking of the diaspora. From the savory and bold flavors of Achari Paneer Pizza to the ultimate home-cooked comfort meal, a pot of Spinach Tadka Dal with rice, Khushbu's recipes are flavor-packed, party-pleasing, and wonderfully surprising. She invites readers on a journey far beyond butter chicken (though she has a stellar recipe for it), offering instructions for preparing meals, drinks, and desserts as diverse as Saag Paneer Lasagna, Classic Dosas, Keralan Fried Chicken Sandwiches, Pani Puri Mojitos, and a Masala Chai Basque Cheesecake. Khushbu makes it easy to dive in, equipping home cooks with a list of simple-to-find pantry staples alongside vibrant images, clever tips and tricks, and illuminating essays that introduce a thrilling voice in American food.